Perception of Air Pollution Health Hazards among Roadside Shop-Keepers in Selected Areas of Bangalore City- Cross Sectional Study - Duraisamy, Shanmugapriya; Narayanappa, Ramakrishna Reddy; Sobagiah, Ranganath Timmanahalli (National Journal of Community Medicine, 2017)
Background: Air Pollution, one of the major avoidable causes of diseases and death globally, has been an increasing issue worldwide. Though anyone can be exposed, people who live near road intersections or who direct traffic are particularly at risk. Proper awareness about the health hazards and the protective measures plays a crucial role in protecting oneself to great extent. Objectives: To assess the Knowledge, Attitude and Practice about health hazards of outdoor air pollution and the prevention of the same among roadside shopkeepers in selected areas in Bangalore. Methodology: Community based Cross sectional study was conducted among 150 roadside shopkeepers near Victoria hospital area in Bangalore using an interview based semi - structured questionnaire. Results: Of the 150 respondents, 65.3% were aware that chronic exposure to air pollution can cause some health hazards and 50% believed it can cause respiratory ailments. However, almost none were aware about other health hazards. Very poor practice regarding personal protection was observed. Attitude towards preventive measures was poor. Conclusion: A major lacunae has been found in both knowledge and attitude towards the health hazards caused by the ambient air pollution necessitating the need for awareness generation and drastic change in practice.